Determinants of Going Concern Audit Opinions: Auditor Reputation Moderation in Indonesian Hospitality Sector - Pasaribu, Muhammad Husein; Erlina; Sadalia, Isfenti (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to empirically examine the influence of Debt Default, Company Growth, Solvency, and Audit Delay on the acceptance of the Going Concern audit opinion. It also evaluates the role of Auditor Reputation as a moderating variable in strengthening or weakening the relationship between the independent variables and the dependent variable. The population consists of all hotel, resort, and cruise ship companies listed on the Indonesia Stock Exchange during the 2019–2023 period, totaling 30 companies. This study uses secondary data obtained from the official website of the Indonesia Stock Exchange, with sample selection conducted using the census sampling technique. Data analysis was carried out using Eviews software. The results indicate that Debt Default (X1), Company Growth (X2), and Solvency (X3) have a positive and significant effect on Going Concern Audit Opinion (Y). Meanwhile, Audit Delay (X4) has a negative but insignificant effect. Furthermore, Auditor Reputation (Z) significantly moderates the relationship between Solvency (X3) and Going Concern Audit Opinion (Y) with a weakening moderation effect, but does not significantly moderate the effects of Debt Default (X1), Company Growth (X2), and Audit Delay (X4).